Accident reconstructions of falls, collisions, and punches in sports. (July 2020) - Kendall, Marshall; Anna Oeur; Brien, Susan E; Cusimano, Michael; Marshall, Shawn; Gilchrist, Michael D; Hoshizaki, Thomas B
Objective: Impacts to the head are the primary cause of concussive injuries in sport and can occur in a multitude of different environments. Each event is composed of combinations of impact characteristics (striking velocity, impact mass, and surface compliance) that present unique loading conditions on the head and brain. The purpose of this study was to compare falls, collisions, and punches from accident reconstructions of sports-related head impacts using linear, rotational accelerations and maximal principal strain of brain tissue from finite element simulation. Methods: This study compared four types of head impact events through reconstruction. Seventy-two head impacts were taken from medical reports of accidental falls and game video of ice hockey, American football, and mixed-martial arts. These were reconstructed using physical impact systems to represent helmeted and unhelmeted falls, player-to-player collisions, and punches to the head. Head accelerations were collected using a Hybrid III headform and were input into a finite element brain model used to approximate strain in the cerebrum associated with the external loading conditions. Results: Significant differences ( p < 0.01) were found for peak linear and rotational accelerations magnitudes (30–300 g and 3.2–7.8 krad/s 2 ) and pulse durations between all impact event types characterized by unique impact parameters. The only exception was found where punch impacts and helmeted falls had similar rotational durations. Regression analysis demonstrated that increases to strain from unhelmeted falls were significantly influenced by both linear and rotational accelerations, meanwhile helmeted falls, punches, and collisions were influenced by rotational accelerations alone. Conclusion: This report illustrates that the four distinct impact events created unique peak head kinematics and brain tissue strain values. These distinct patterns of head acceleration characteristics suggest that it is important to keep in mind that head injury can occur from a range of low to high acceleration magnitudes and that impact parameters (surface compliance, striking velocity, and impact mass) play an important role on the duration-dependent tolerance to impact loading.